The military-political situation in Central Asia in the context of the growing instability in Afghanistan - Z. A. Kokoshina (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Central Asian region due to its economic potential and strategic signiﬁ -cance has traditionally been of particular importance for Russia’s foreign policy. It was therefore not surprising that a serious deterioration of the political situation in Afghanistan in summer-autumn 2021 caused by the military defeat and the subsequent collapse of the pro-Western regime followed by the seizure of power by the Taliban raised serious concern of the Russian leadership. The developments in Afghanistan have attracted an increasing attention of the expert community, prompting a ﬂ urry of comments and forecasts. Although many of these papers were published hastily, their assessments and conclusion were usually based on the long-term observations. This paper attempts to provide an overview of the military-political situation in the Central Asian region as it was caught by a new crisis in Afghanistan and as it is seen by both Russian and foreign experts. The ﬁ rst section outlines positions and interests of the key regional and non-regional actors that have a signiﬁ cant impact on the military-political situation in Central Asia. The second section examines the response of the Russian Federation to the situation in Afghanistan after the Taliban took power. Finally, the third section provides an overview of the latest expert comments and reports that attempt to assess possible implications of those events for the regional military-political dynamics and the national security interests of the Russian Federation.